Application of C4.5 Algorithm for Simulation of Prediction of Victory in Acceptance of Several Prospective Employees - Marpaung, Preddy (Information Technology and Science (ITScience), 2019)
Employees as individual who work for employer, Based on agreement and work agrements both written and unwritten, to carry out a job in a certainposition or activityby obtaining compensation paid based on a certain period, Job adjustments or other Provisions applied by the employer. Including individuals who do woork in public office,and it can be assumed that employeses are all residents who can do work and get a salary every mount, Both at school and company and school also require several new employees who will be placed as teachers in the field of sport. Therefore we need method or method to indentify prospective new employees in the field of sport at school. This was done to get the creteria needed by the school. C4.5 Algorithm can be used to make predictions or clafication of prospective new employees who want to join ABC school using the concept of entropy and gain.